Prevalence and Clinical Significance of Postpartum Endometritis and Wound Infection. Issue 2 (2000) - Chaim, Walter; Bashiri, Asher; Bar-David, Juri; Shoham-Vardi, Ilana; Mazor, Moshe
Abstract : Objective: To correlate clinical variables (gestational age, severe pregnancy-induced hypertension, gestational diabetes mellitus, history of previous cesarean sections, fetal distress, perinatal mortality, postpartum anemia, Apgar score ≤3 at 1 minute and ≤7 at 5 minutes, and instrumental delivery) with postpartum endometritis (PPE) and wound infection. Methods: Descriptive cross-sectional study of the outcome of 75, 947 term and preterm singleton deliveries; vaginally and by cesarean section from 1989–1997. Results: The prevalence of PPE after vaginal deliveries was 0.17% (120/68, 273). Gestational age of less than 37 weeks, severe pregnancy-induced hypertension, fetal distress, instrumental deliveries, neonatal mortality, postpartum anemia, and Apgar scores of <7 after 5 minutes were significantly associated with PPE. Gestational diabetes and an Apgar score of <3 after 1 minute showed similar frequency with and without PPE. The prevalence of PPE after cesarean section was 2.63% (202/7, 677). Preterm cesarean sections, history of previous cesarean sections, anemia, and low Apgar scores were seen more frequently with PPE than without. The incidence of cesarean delivery with gestational diabetes mellitus, fetal distress, and perinatal mortality was similar in presence and absence of PPE. The rate of wound infection after cesarean section was 3.97% (318/7, 995). Gestational diabetes mellitus, history of previous cesarean deliveries, and low Apgar scores were significantly more frequent with than without wound infection. Gestational age, severe pregnancyinduced hypertension, fetal distress, perinatal mortality, and postpartum anemia were not associated with wound infection. Conclusions: Awareness of the aforementioned associations may prevent and shorten hospital stay by early diagnosis and appropriate treatment. Infect. Dis. Obstet. Gynecol. 8:77–82; 2000.